Improving Reading Interest of Net Generation Cadets Through the Development of Innovative Library Facilities and Infrastructure - Endrawati, Rizki Ocsera; Rumani, Daniel Dewantoro; Hariri, Ahmad; Prasojo, Genny Luhung; Wibowo, Untung Lestari Nur (Yayasan Sinergi Kawula Muda, 2023)
This study explores boosting the reading interest of net generation cadets through innovative library facility and infrastructure development. The independent variable is library facility and infrastructure development, while the dependent variable is next generation cadets' reading interest. Quantitative research employing the Likert scale gathered data from Indonesian Flight Academy cadets in Banyuwangi. Descriptive analysis reveals a positive impact of library facility and infrastructure development on cadets' reading interest, supported by high mean and median values. Inferential statistical analysis further confirms a significant relationship between these factors. These findings significantly contribute to understanding factors influencing net generation cadets' reading interest. Practical implications advocate increased investment in innovative library facility and infrastructure, including relevant book additions, technology for information access, and comfortable reading spaces. Identifying additional influencing factors and promoting literacy programs and reading habit development are recommended. In conclusion, innovative library facility and infrastructure development critically enhance net generation cadets' reading interest. Regular evaluation and updates of implemented facilities, programs, and policies are essential, requiring collaboration among educational institutions, libraries, government, and the community for optimal results in improving reading interest. in one or two sentences.